Cell-To-Cell Communication in Bilateral Macronodular Adrenal Hyperplasia Causing Hypercortisolism - Lefebvre, Hervé; Duparc, Céline; Prévost, Gaëtan; Bertherat, Jérôme; Louiset, Estelle (Frontiers in Endocrinology, 2015)
It has been well established that, in the human adrenal gland, cortisol secretion is not only controlled by circulating corticotropin but is also influenced by a wide variety of bioactive signals, including conventional neurotransmitters and neuropeptides, released within the cortex by various cell types such as chromaffin cells, neurons, cells of the immune system, adipocytes and endothelial cells. These different types of cells are present in bilateral macronodular adrenal hyperplasia, a rare etiology of primary adrenal Cushing’s syndrome, where they appear intermingled with adrenocortical cells in the hyperplastic cortex. In addition, the genetic events which cause the disease favor abnormal adrenal differenciation that results in illicit expression of paracrine regulatory factors and their receptors in adrenocortical cells. All these defects constitute the molecular basis for aberrant autocrine/paracrine regulatory mechanisms which are likely to play a role in the pathophysiology of bilateral macronodular adrenal hyperplasia-associated hypercortisolism. The present review summarizes the current knowledge on this topic as well as the therapeutic perspectives offered by this new pathophysiological concept.